Membingkai Kepatuhan sebagai Modal: Peran Komunikasi Strategis dan Pemasaran Layanan Digital dalam Menerjemahkan Inovasi Berbasis Regulasi menjadi Kinerja Keuangan di Sektor Maritim Indonesia - Reffangga Nandya Bimantara; Inayatur Robbany; Lili Purnamasita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The global maritime industry currently faces immense financial pressure due to stringent international regulatory mandates, such as MARPOL and STCW. Traditionally, investments for such compliance are viewed by management merely as cost centers that burden corporate profitability without clear return on investment. This study aims to critically investigate how Class 1 shipping and port companies in Indonesia transform these mandatory technology investments into strategic assets through corporate communication mechanisms. Employing a double descriptive qualitative case study design, this research applies rigorous data triangulation by combining the analysis of financial reports, sustainability reports, and in-depth interviews with six financial unit team coordinators as key informants. The analysis reveals that companies with superior financial performance do not separate technical compliance functions from commercial strategies. Instead, they proactively integrate strategic communication and digital marketing into their technology budget planning from the outset. This strategy allows companies to